Changes in Consumer Food Preferences in EU Countries from 2001-2013 - Grzegorz Koszela; Luiza Ochnio (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
This paper attempts to rank EU countries according to changes in consumer food preferences between 2001 and 2013. The size of these changes was determined using a synthetic rate created for this purpose. This rate was intended to accommodate changes in consumption levels in 9 product groups per capita. It turns out that we may use the greatest possible measure of the structure’s dissimilarity as an analogy to the Gini coefficient, to express this rate. Using the “ar” measure to compare structures of food consumption in two separate three-year time periods for each country, scientists may rank and group the countries according to the value of changes in consumer food preferences.